Energy and exergy analyses of drying of red pepper slices in a convective type dryer - Akpinar, EK (Pergamon-Elsevier Science Ltd, 2004)
In this paper, the energy and exergy analyses of the drying process of thin layer of red pepper slices are investigated. Drying experiments were conducted at inlet temperatures of drying air of 55, 60 and 70 degreesC and at a drying air velocity of 1.5 m/s in a convective type dryer. Using the first law of thermodynamics, energy analysis was carried to estimate the ratios of energy utilization. However, exergy analysis was accomplished to determine type and magnitude of exergy losses during the drying process by applying the second law of thermodynamics. (C) 2004 Elsevier Science Ltd.
Keywords: Particles